2021
DOI: 10.5198/jtlu.2021.1789
|View full text |Cite
|
Sign up to set email alerts
|

relationship between urban form and mode choice in US and Mexican cities: A comparative analysis of workers’ commutes

Abstract: This paper examines empirical relationships among commuters’ mode choice, metropolitan urban form, and socioeconomic attributes in the 100 largest urban areas in the United States and Mexico. Fitting multinomial logit models to data for more than 5 million commuters and their home urban area, we find several consistent relationships and several important differences in relationships among urban form and travel behavior. In both countries, urban residents living in housing types associated with more centrally l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
0
2
1
3
Order By: Relevance
“…Also, it is an indication that public transport holds great potentials in providing a sustainable transport system in the city. However, the outcome of this result differs from the existing studies (Al-Salh & Esztergas-Kiss, 2021; Drliciak et al, 2020; Guerra & Li, 2021; Novačko et al, 2020; Obaid & Hamad, 2020) found the USA,, Europe, and Middle east which indicate that private transport was the most preferred mode for intra urban trips.…”
Section: Discussioncontrasting
confidence: 88%
See 1 more Smart Citation
“…Also, it is an indication that public transport holds great potentials in providing a sustainable transport system in the city. However, the outcome of this result differs from the existing studies (Al-Salh & Esztergas-Kiss, 2021; Drliciak et al, 2020; Guerra & Li, 2021; Novačko et al, 2020; Obaid & Hamad, 2020) found the USA,, Europe, and Middle east which indicate that private transport was the most preferred mode for intra urban trips.…”
Section: Discussioncontrasting
confidence: 88%
“…Most of the plethora of studies on the modal split of intra urban trips found in the literature focused on Europe, America and Southeast Asia with little emphasis on Africa. These studies (such as Bucsky, 2020; Chen et al, 2015; Drliciak et al, 2020; Guerra & Li, 2021; Novačko et al, 2020; Li et al, 2021; Mendiola & Gonzalez, 2021; Shukla, 2019) explains the modal split of intra urban trips and its causal factors. The outcome of most of these studies show private transport as a popular mode used for intra urban trips in their respective cities.…”
Section: Introductionmentioning
confidence: 99%
“…Existe uma extensa literatura sobre como a organização espacial das cidades influencia a mobilidade urbana (Ewing e Cervero, 2010;Lohrey e Creutzig, 2016;Stevens, 2017). Por exemplo, diversos estudos analisam como a forma urbana impacta o comportamento de viagem das pessoas, seja induzindo percursos mais curtos/longos (Ewing, Tian e Lyons, 2018; Lee e Lee, 2020; Van de Coevering e Schwanen, 2006;Liu e Shen, 2011), influenciando na escolha do modo de transporte (Bento et al, 2005;Buehler, 2011;Guerra e Li, 2021) ou afetando os tempos despendidos 2 8 0 2 no trajeto (Jun, 2020;Muñis e Galindo, 2005). Alguns trabalhos analisam ainda como o desempenho e a viabilidade econômica de sistemas de transporte público são afetados pela densidade populacional e mix de uso do solo (Cooke e Behrens, 2017;Lee e Bencekri, 2021).…”
Section: Revisão De Literaturaunclassified
“…Muitos desses estudos utilizam modelos de regressão multinível para captar como o padrão de viagens das pessoas é afetado tanto por características do ambiente construído local quanto por características da forma urbana na escala metropolitana. (Ewing et al, 2015;Guerra e Li, 2021;Hong, Shen e Zang, 2014; Lee e Lee, 2020;Zhao, Diao e Li, 2017).…”
Section: Revisão De Literaturaunclassified
See 1 more Smart Citation